Pemberian Storytelling audio visual dalam menurunkan tingkat kecemasan anak usia pra sekolah akibat Hospitalisasi - Sri Damayanti; Rahmawati Ramli; Rizqy Iftitah Alam; Sunarti (Window of Nursing Journal, 2026)
Hospitalization or being admitted to the hospital often makes preschool children cry, refuse food or medicine, and generally be uncooperative. The anxiety experienced by children undergoing treatment can be reduced through distractions like music therapy, play therapy, relaxation, and storytelling. Storytelling is a powerful technique to distract children from anxiety. In this case, storytelling can convey certain messages to children so they can show better cooperation. The purpose of this study is to find out the effect of audiovisual storytelling on the anxiety level of preschool children due to hospitalization. This study uses quantitative research with a population of 186, and in this study, the researcher only intervened with one treatment group consisting of 40 children. The design used was a pre-experimental one with a one-group pretest and posttest approach and was tested using a Paired T-Test. Audio-visual storytelling therapy found that 22 preschool children experienced mild anxiety before the intervention, with a result of 55.0%, and after the audio-visual storytelling intervention, 30 preschool children treated in the hospital did not suffer from anxiety, with a result of 75.0%. Based on the analysis, a p-value of 0.000 < 0.05 and a Z value of 9.427 were found. The results show that the p-value is smaller than alpha, so HO is rejected. This indicates that there is a difference in anxiety in preschool children before and after storytelling therapy. It is hoped that future researchers can increase the sample size and conduct interventions with better media.